2016
DOI: 10.1111/jep.12504
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pharmacist‐based compared to doctor‐based anticoagulation management in Qatar

Abstract: Data from 278 patients taking warfarin (78 managed at pharmacist and 200 at doctor-based clinic) were evaluated. Subjects followed at the pharmacist-based clinic had a superior TTR compared to those managed at the doctor-based clinic (81.8% vs. 69.8%, P < 0.001). Additionally, the percentage of visits within therapeutic range were significantly higher in the pharmacist's group compared to doctor's group (76.5% vs. 71.2%, P = 0.011). At the same time, percentage of visits with extreme subtherapeutic INR was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…The current finding is supported by several previous investigations [22][23][24][25] 25 respectively clearly support the results of the present study. All evidences necessitate the collaborative role of clinical pharmacist intervention in order to achieve optimal INR levels in the patients with warfarin therapy.…”
Section: Fig 1: the Percentage Of Patients With Inr Within The Targesupporting
confidence: 83%
“…The current finding is supported by several previous investigations [22][23][24][25] 25 respectively clearly support the results of the present study. All evidences necessitate the collaborative role of clinical pharmacist intervention in order to achieve optimal INR levels in the patients with warfarin therapy.…”
Section: Fig 1: the Percentage Of Patients With Inr Within The Targesupporting
confidence: 83%
“…There were 17 studies (11,12,14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), including 8 RCTs (14,15,(22)(23)(24)(25)(26)(27), and 9cohort studies (11,12,(28)(29)(30)(31)(32)(33)(34), and 9919 patients involved in total. Our research showed that lower risk of total haemorrhage events, minor haemorrhage events and thrombosis events in pharmacist-led management group, but the percentage of time within target therapeutic range and the percentage of time within the expanded therapeutic range, major haemorrhage events and mortality were not significantly different between pharmacist-led management model and other management models.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with former reviews, we searched relevant articles more comprehensively and updated some new and high quality studies (29)(30)(31)(32)(33)(34) into the review. We reviewed outcomes TTR, TER, haemorrhage events (total, minor, major), thrombosis events, mortality, patient satisfaction and cost saving, which were more considerately and precisely than former reviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies have focused on outcomes related to pharmacist and physician anticoagulation care, sparse literature directly compares outcomes of systematic anticoagulation management in pharmacist‐ vs nurse‐managed clinics. At the University of Illinois Hospital and Health Sciences System (UI Health) systematic anticoagulation management is provided via two models of care, a pharmacist‐managed anticoagulation clinic (PMAC) and a nurse‐managed anticoagulation clinic (NMAC).…”
Section: Introductionmentioning
confidence: 99%